El Palacio de las Cortes de Madrid visto por Elías Andrés y Victoria Prego (La Transición, TVE, 1993) : un teatro para la Transición (1975-1981) - Nancy Berthier (Cahiers de Civilisation Espagnole Contemporaine)
The Transition supposed a reappropriation of Madrid’s urban space under the sign of a freedom gradually found. The city then turned into a gigantic «stage» for democratization. Because of its emblematic role, the Palace of the Cortes occupied a special place in this process and was widely filmed. What helped anchor it in the collective imagination as the quintessential space for the democratization of the country was the subsequent recycling of filmed images, the meaning of which was reworked a posteriori. The one proposed by the documentary series La Transición (1993, Elías Andrés, Victoria Prego) is particularly significant in this respect. The a priori cold and boring place of political rationality is transformed into a real theater of democratization in three acts where politicians become characters in an emotionally charged drama, but with a happy ending.